2019
DOI: 10.4149/neo_2018_181010n754
|View full text |Cite
|
Sign up to set email alerts
|

ASXL1 gene alterations in patients with isolated 20q deletion

Abstract: Deletion 20q is a recurrent abnormality in myeloid malignancies. In our previous study, we identified fusion of additional sex combs-like 1 (ASXL1) and teashirt zinc finger homeobox 2 genes in a patient with myelodysplastic syndrome. The objective of this study was to determine the frequency of ASXL1 breakpoints in a cohort of 36 patients with deletion 20q as the sole cytogenetic aberration. A combination of molecular cytogenetic methods was used to confirm ASXL1 gene alterations in 19 of the 36 patients and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The incidence and prognostic impact of ASXL1 chromosomal deletions have been partially analysed. Brezinova et al 8 . observed a negative clinical impact of ASXL1 chromosomal deletion in patients with myeloid neoplasms and del(20q).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and prognostic impact of ASXL1 chromosomal deletions have been partially analysed. Brezinova et al 8 . observed a negative clinical impact of ASXL1 chromosomal deletion in patients with myeloid neoplasms and del(20q).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The incidence and prognostic impact of ASXL1 chromosomal deletions have been partially analysed. Brezinova et al 8 observed a negative clinical impact of ASXL1 chromosomal deletion in patients with myeloid neoplasms and del(20q). However, the robustness of the results was limited by the low number of patients included and the heterogeneity of their pathology.…”
Section: Introductionmentioning
confidence: 99%
“…This has also been correlated with a lower platelet count and a poor response to azacytidine (AZA) [ 44 ]. The ASXL1 mutations are found in 11 to 21% of patients with MDS and are a predictor of poor OS [ 45 , 46 , 47 ]. The median survival of patients with del(20q) was 54 months, compared with 12 months in the patients with del(20q) plus other additional chromosomal abnormalities [ 48 ].…”
Section: Cytogeneticsmentioning
confidence: 99%